A tough trade-off? The asymmetrical impact of populist radical right inclusion on satisfaction with democracy and government. Issue 1 (6th February 2021) - Harteveld, Eelco; Kokkonen, Andrej; Linde, Jonas; Dahlberg, Stefan
Abstract: Populist radical right (PRR) parties are increasingly included in coalition governments across Western Europe. How does such inclusion affect satisfaction with democracy (SWD) in these societies? While some citizens will feel democracy has grown more responsive, others will abhor the inclusion of such controversial parties. Using data from the European Social Survey (2002–2018) and panel data from the Netherlands, we investigate how nativists' and non-nativists' SWD depends on mainstream parties' strategies towards PRR parties. We show that the effect is asymmetrical: at moments of inclusion nativists become substantially more satisfied with democracy, while such satisfaction among non-nativists decreases less or not at all. This pattern, which we attribute to Easton's 'reservoir of goodwill', that is, a buffer of political support generated by a track-record of good performance and responsiveness, can account for the seemingly contradictory increase in SWD in many Western European countries in times of populism.